The transcriptional coordination of functional gene clusters is dependent on multiple chromatin remodelers in a haploid strain of the budding yeast, Saccharomyces cerevisiae - Baadani, Abtsam A.; Coon, Gabrielle F.; Bui, Christopher; Chidester, Mary C.; Eldabagh, Reem S.; Arnone, James T. (Frontiers in Fungal Biology, 2025)
The organization of functionally related gene families oftentimes exhibits a non-random genomic distribution as gene clusters that are prevalent throughout divergent eukaryotic organisms. The molecular and cellular functions of the gene families where clustering has been identified vary, and include those involved in basic metabolism, secondary metabolite biosynthesis, and large gene families (e.g. ribosomal proteins). Many of these gene families exhibit transcriptional coregulation, however the roles that clustering plays and the mechanism(s) underlying co-expression are currently understudied. A comprehensive characterization of these relationships would allow for a greater understanding of the implications of genetic editing and engineering to minimize undesired consequences. Here we report the impact of gene clustering and genomic positioning on the expression of large, coregulated gene families in a haploid strain of the budding yeast, Saccharomyces cerevisiae. Computational analysis identifies a significant and complex role for chromatin remodeling as a mechanism underlying cluster transcription. Functional dissection of the ‘vitamin metabolic process’, ‘ribosome biogenesis’, and ‘ribosomal protein’ gene families, characterized the roles for SNF2, JHD2, HIR2, EAF3, and yKU70 dependent chromatin remodeling during steady state transcription as well as the transcriptional response to glucose replenishment. Finally, mining and analysis of transcription profiles reveals significant transcriptional differences between the clustered and unclustered subsets within coregulated families under specific stressors.